Small-scale farmers' perceptions and knowledge of tree intercropping systems in the Khorezm region of Uzbekistan - Kan, E; Lamers, John P.A; Eshchanov, R; Khamzina, A (Forests, trees and livelihoods, 2008)
Despite compelling evidence supporting the contribution of Tree Intercropping Systems (TIS) to farmers' livelihoods, little research has addressed farmers' knowledge of TIS in the ecologically deteriorated zones of Uzbekistan, Central Asia. Similarly, farmers' understanding of the motivation for practicing TIS is poorly known. A survey conducted with 133 households during 2003-2005 showed that the surveyed farmers managed 17 different tree-crop simultaneous systems with 97% of all sites including fruit species. The annual components were commercially the more important and were given the highest priority-with cereals (47%), vegetables (27%), fodder (19%) and cash crops (7%). Irrespective of tree species and plantation age, the most frequently observed tree density was 200-500 trees ha −1 , although subject to large variations. The dominance of younger trees <10 years (41%) was evidence of the recent interest in TIS and was obviously linked to recent land reforms and change in land ownership. The knowledge of TIS management among those surveyed was rather superficial. Training and educating of farmers and gardeners would help to achieve the potential benefits of TIS. The interaction between agroforestry, environmental research and farmers' practices must be improved given the growing interest and significance of TIS for the rural population, and the government must increase private landowners' participation in farm management and decision-making.